2015
DOI: 10.2147/ndt.s87596
|View full text |Cite
|
Sign up to set email alerts
|

Disturbed spontaneous brain activity pattern in patients with primary angle-closure glaucoma using amplitude of low-frequency fluctuation: a fMRI study

Abstract: ObjectiveThe aim of this study is to use amplitude of low-frequency fluctuation (ALFF) as a method to explore the local features of spontaneous brain activity in patients with primary angle -closure glaucoma (PACG) and ALFFs relationship with the behavioral performances.MethodsA total of twenty one patients with PACG (eight males and 13 females), and twenty one healthy subjects (nine males and twelve females) closely matched in age, sex, and education, each underwent a resting-state functional magnetic resonan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
36
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 34 publications
(44 reference statements)
3
36
2
Order By: Relevance
“…Li et al observed that POAG relative to NCs demonstrated significant decreased amplitude of low-frequency fluctuation (ALFF)/fractional ALFF (fALFF) values in the visual cortices, posterior regions of the default-mode network, and motor and sensory cortices, and showed significant increased ALFF/fALFF values in the prefrontal cortex, left superior temporal gyrus, right middle cingulate cortex, and left inferior parietal lobule 12. Furthermore, only one study explored the regional spontaneous brain changes in PACG relative to NCs, showing significant lower ALFF values in the left precentral gyrus, bilateral middle frontal gyrus, bilateral superior frontal gyrus, right precuneus, and right angular gyrus, and higher ALFF value in the right precentral gyrus 13. Although these rsfMRI studies provided evidence for the fact that glaucoma is associated with abundant disturbed regional brain activity, a fundamental understanding of the underlying neural mechanism of optic neuropathy and regional spontaneous brain changes caused by glaucoma remains to be further explored, especially for PACG.…”
Section: Introductionmentioning
confidence: 99%
“…Li et al observed that POAG relative to NCs demonstrated significant decreased amplitude of low-frequency fluctuation (ALFF)/fractional ALFF (fALFF) values in the visual cortices, posterior regions of the default-mode network, and motor and sensory cortices, and showed significant increased ALFF/fALFF values in the prefrontal cortex, left superior temporal gyrus, right middle cingulate cortex, and left inferior parietal lobule 12. Furthermore, only one study explored the regional spontaneous brain changes in PACG relative to NCs, showing significant lower ALFF values in the left precentral gyrus, bilateral middle frontal gyrus, bilateral superior frontal gyrus, right precuneus, and right angular gyrus, and higher ALFF value in the right precentral gyrus 13. Although these rsfMRI studies provided evidence for the fact that glaucoma is associated with abundant disturbed regional brain activity, a fundamental understanding of the underlying neural mechanism of optic neuropathy and regional spontaneous brain changes caused by glaucoma remains to be further explored, especially for PACG.…”
Section: Introductionmentioning
confidence: 99%
“…The ALFF has been widely applied to detect the brain function within a specific frequency range (0.01–0.08 Hz) 17. In our previous studies, the ALFF method was successfully used to assess the neurological conditions in some eye diseases such as optic neuritis,18 glaucoma,19 and comitant strabismus 20. Our study is the first to use the ALFF method to investigate the spontaneous brain activity in HM patients and investigate its relationship with the behavioral performances.…”
Section: Introductionmentioning
confidence: 99%
“…A previous study has shown that the reliable propagation of synchronous neural activity is crucial for neural information processing. 13 The regional homogeneity (ReHo) method, a widely used resting-state fMRI measure, has been used to explore the local synchronization of spontaneous fMRI signals by calculating Kendall’s coefficient concordance of the time series of dynamic fluctuations of voxels within a given cluster, providing important information on brain activity. 14 , 15 However, cerebral dysfunction may lead to altered neuronal synchrony, which will have an adverse effect on neural information processing.…”
Section: Introductionmentioning
confidence: 99%